A nanofiber composite aerogel and its preparation method and application
Through the composite and directional freezing technology of paraffin-silica microcapsules and methyltrimethoxysilane and bacterial cellulose, nanofiber composite aerogel with high resilience and excellent oil-water separation performance was prepared, and bacterial cellulose was solved. The problem of insufficient mechanical properties of aerogels has achieved more efficient liquid separation and adsorption effects.
Patent Information
- Application Number
- CN202410828750.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-25
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-06-25
AI Technical Summary
The mechanical properties of existing bacterial cellulose aerogels are not high enough to meet certain application needs.
Paraffin-silica microcapsules and methyltrimethoxysilane were used to compound with bacterial cellulose, and nanofiber composite aerogels were prepared through directional freezing and freeze-drying techniques to form a large pore-oriented structure to improve mechanical properties and adsorption properties.
It significantly improves the elasticity, hydrophobicity and oil-water separation performance of nanofiber composite aerogel, enhances its adsorption ability and recycling as an adsorption material, and simplifies the preparation process and is suitable for industrial production.
Smart Images

Figure CN118767882B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of aerogels, and in particular to a nanofiber composite aerogel and a preparation method and application thereof. Background Art
[0002] The nanoporous network structure of aerogel itself gives it excellent properties such as high porosity, high specific surface area, and low density. Compared with two-dimensional membrane materials, three-dimensional aerogel has both adsorption and separation capabilities, and can effectively solve the problem of dense structure and "high efficiency and low resistance" of two-dimensional membrane materials. Therefore, it is widely favored by researchers in the field of oil-water separation.
[0003] Bacterial cellulose is a nano-scale cellulose with a wide source, green, sustainable and biodegradable. There are a large number of hydroxyl groups on its macromolecules, and the molecular chain is easy to form intramolecular and intermolecular hydrogen bonds. At the same time, hydroxyl groups can react with other groups such as acid hydrolysis, cross-linking, esterification, silanization, etc., making cellulose easy to be modified, thereby improving practical performance. As a nanocellulose, bacterial cellulose has other favorable properties on top of the above basic properties of cellulose, including high specific surface area, high crystallinity, purity, biocompatibility, biodegradability, amphiphilicity, surface chemical modification reactivity, barrier properties, favorable optical and mechanical strength. Importantly, compared with other types of nanocellulose, bacterial cellulose aerogel does not need to be dissolved and gelled, which greatly simplifies the experimental steps. Therefore, based on the green and environmentally friendly environment, bacterial cellulose aerogel can be used as an ideal adsorption material and oil-water separation material.
[0004] However, the mechanical properties of current bacterial cellulose aerogels, such as resilience, are not high enough. Therefore, it is necessary to improve the existing bacterial cellulose aerogels. Summary of the invention
[0005] The object of the present invention is to provide a nanofiber composite aerogel and a preparation method and application thereof, so as to solve or at least partially solve the problems existing in the prior art.
[0006] In a first aspect, the present invention provides a method for preparing a nanofiber composite aerogel, comprising the following steps:
[0007] After paraffin, water and ethanol are mixed, the paraffin is heated to melt, tetraethyl orthosilicate and hexadecyltrimethylammonium bromide are added for emulsification, and then ammonia water is added for reaction, filtered, washed and dried to obtain paraffin-silicon dioxide microcapsules;
[0008] paraffin-silica microcapsules, methyltrimethoxysilane and ethanol are mixed, heated, and then water and ammonia water are added to react, filtered, washed and dried to obtain hydrophobic paraffin-silica microcapsules;
[0009] adding bacterial cellulose into water to obtain a bacterial cellulose dispersion;
[0010] After mixing methyltrimethoxysilane, water, tert-butyl alcohol and citric acid, the bacterial cellulose dispersion is added and the stirring is continued to obtain a bacterial cellulose-methyltrimethoxysilane dispersion;
[0011] Adding hydrophobic paraffin-silica microcapsules to a mixed solution of tert-butyl alcohol and water, dispersing by ultrasonication, and then adding bacterial cellulose-methyltrimethoxysilane dispersion to obtain a mixed solution;
[0012] The mixed solution is sequentially subjected to directionally freezing and freeze-drying to obtain a nanofiber composite aerogel.
[0013] Preferably, paraffin, water and ethanol are mixed, heated to 50-90° C. to melt the paraffin, and then tetraethyl orthosilicate and hexadecyltrimethylammonium bromide are added and emulsified at 400-1000 r / min for 30-60 min, and then ammonia water is added, reacted at 300-500 r / min for 1-2 h, filtered, washed and dried to obtain paraffin-silicon dioxide microcapsules; wherein the mass volume ratio of paraffin, tetraethyl orthosilicate, hexadecyltrimethylammonium bromide, water, ethanol and ammonia water is (1-3) g: (1-3) g: (0.5-2) g: (55-60) mL: (25-30) mL: (0.5-2) mL, and the mass concentration of ammonia water is 20-30%.
[0014] Preferably, paraffin-silica microcapsules, methyltrimethoxysilane and ethanol are mixed, heated to 40-60° C., water and ammonia water are added, reacted at 300-500 r / min for 10-15 hours, filtered, washed and dried to obtain hydrophobic paraffin-silica microcapsules; wherein the mass volume ratio of paraffin-silica microcapsules, methyltrimethoxysilane, ethanol, water and ammonia water is (1-4) g: (1-4) g: (55-65) g: (1-8) g: (0.5-2) mL, and the mass concentration of ammonia water is 20-30%.
[0015] Preferably, the mass concentration of the bacterial cellulose dispersion is 0.35-0.7%.
[0016] Preferably, methyltrimethoxysilane, water, tert-butyl alcohol and citric acid are stirred at 350-400 r / min for 40-50 min to obtain a methyltrimethoxysilane dispersion;
[0017] The methyltrimethoxysilane dispersion liquid is mixed with the bacterial cellulose dispersion liquid, and ultrasonically dispersed for 40 to 70 minutes to obtain a bacterial cellulose-methyltrimethoxysilane dispersion liquid;
[0018] Wherein, the mass ratio of methyltrimethoxysilane, water, tert-butyl alcohol and citric acid is (0.1-0.2):(5-6):(5-6):(0.04-0.05);
[0019] The mass ratio of methyltrimethoxysilane in the methyltrimethoxysilane dispersion to bacterial cellulose in the bacterial cellulose dispersion is (3-4):5.
[0020] Preferably, the hydrophobic paraffin-silicon dioxide microcapsules are added to a mixed solution of tert-butyl alcohol and water, ultrasonically dispersed for 20 to 30 minutes, and then the bacterial cellulose-methyltrimethoxysilane dispersion is added, and stirred at 350 to 400 r / min for 50 to 70 minutes to obtain a mixed solution;
[0021] Wherein, the mass ratio of hydrophobic paraffin-silica microcapsules, tert-butyl alcohol, and water is (0.1-0.135):(4-5):(4-5);
[0022] The mass ratio of hydrophobic paraffin-silica microcapsules to bacterial cellulose is (0.1-3):5.
[0023] Preferably, the directional freezing specifically includes:
[0024] The mixed liquid is placed in a mold, and the bottom of the mold is placed in a cold source for directional freezing;
[0025] The mold is made of heat-conducting metal, the cold source is liquid nitrogen, and the directional freezing time is 5 to 15 minutes.
[0026] Preferably, the freeze-drying temperature is -20 to -60°C, and the freeze-drying time is 24 to 72 hours.
[0027] In a second aspect, the present invention also provides a method for preparing a nanofiber composite aerogel, which is prepared by the preparation method.
[0028] In a third aspect, the present invention also provides a nanofiber composite aerogel prepared by the preparation method or the use of the nanofiber composite aerogel as an adsorption material or an oil-water separation material.
[0029] The present invention has the following beneficial effects compared with the prior art:
[0030] 1. The preparation method of the nanofiber composite aerogel of the present invention, the selected bacterial cellulose is a kind of nanocellulose, which comes from microorganisms and has the advantages of wide sources, biodegradability, high purity, good mechanical properties, etc. And its surface has abundant hydroxyl groups, which makes it amphiphilic, and it is easy to undergo acid hydrolysis, cross-linking, esterification, silanization and other reactions to modify and improve practical performance. Bacterial cellulose aerogel combines the advantages of aerogel and bacterial cellulose, and has the advantages of low density, high porosity, high specific surface area, etc. There are many "pores" inside it. This structure provides a separation channel for separating liquids and provides abundant adsorption sites for adsorbing liquids; the present invention uses directional freezing to obtain a macroporous oriented structure, so that the microcapsule / bacterial cellulose-methyltrimethoxysilane macroporous oriented nanofiber composite aerogel has a higher specific surface area, significantly reducing the liquid passing path to improve the flux of the composite aerogel, and compared with the non-macroporous oriented microcapsule / bacterial cellulose-methyltrimethoxysilane composite aerogel, the adsorption performance and oil-water separation performance of the oriented nanofiber composite aerogel are significantly improved. Moreover, the microcapsule / bacterial cellulose-methyltrimethoxysilane macroporous oriented nanofiber composite aerogel provided by the present invention also has a multi-level pore structure and fine nanofibers, which can provide more adsorption sites, can effectively adsorb organic matter in oily wastewater, and improve the oil-water separation performance and adsorption performance of the composite aerogel; in the process of obtaining the macroporous oriented structure by directional freezing, methyltrimethoxysilane tends to be concentrated at the nodes of the bacterial cellulose nanofibers. When the composite aerogel is subjected to external pressure, the stress is first concentrated at the nodes, which effectively alleviates the stress breakage of the bacterial cellulose nanofibers, so that the composite aerogel has excellent resilience, and at the same time gives the composite aerogel excellent hydrophobicity and recyclability; the microcapsule is coated on the nanofiber to form a re-entrant cavity structure, which is more conducive to the formation of a stable liquid film after the aerogel is pre-wetted by the liquid, reaching a metastable state, thereby hopefully realizing underwater dual super-superphobicity;
[0031] 2. The preparation method of the nanofiber composite aerogel of the present invention has a simple preparation process, is easy to operate, has low toxicity of the preparation raw materials, is green and environmentally friendly, has low production cost, and is suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the prior art descriptions. Obviously, the drawings described below are only some embodiments of the present invention, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0033] Figure 1 For the PW@SiO prepared in Examples 1 to 4 and Comparative Example 1 2 -SEM images of MTMS;
[0034] Figure 2 The scanning electron microscope images of the nanofiber composite aerogels prepared in Examples 1 to 4 and Comparative Example 1 at different magnifications;
[0035] Figure 3 The contact angle test results of the nanocomposite aerogels prepared in Examples 1 to 4 and Comparative Example 1 are shown;
[0036] Figure 4 The oil-water separation test results of the composite aerogels prepared in Examples 1 to 3 and Comparative Example 1 are shown;
[0037] Figure 5 This is the adsorption performance test result diagram of PCM / BC-MTMS-50;
[0038] Figure 6 This is a graph showing the resilience test results of the composite aerogels prepared in Examples 1 to 4 and Comparative Example 1. DETAILED DESCRIPTION
[0039] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0040] It should be noted that the order of description of the following embodiments is not intended to limit the preferred order of the embodiments. In addition, in the description of the present application, the term "including" means "including but not limited to". Various embodiments of the present invention may be in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity and should not be understood as a rigid limitation on the scope of the present invention; therefore, it should be considered that the range description has specifically disclosed all possible sub-ranges and single numerical values within the range. For example, it should be considered that the range description from 1 to 6 has specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the numbered ranges, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated in this article, it is meant to include any cited numbers (fractions or integers) within the indicated range.
[0041] The present invention provides a method for preparing a nanofiber composite aerogel, comprising the following steps:
[0042] S1, paraffin, water and ethanol are mixed, heated to melt the paraffin, tetraethyl orthosilicate and hexadecyltrimethylammonium bromide are added for emulsification, and then ammonia water is added for reaction, filtered, washed and dried to obtain paraffin-silicon dioxide microcapsules;
[0043] S2, mixing paraffin-silica microcapsules, methyltrimethoxysilane and ethanol, heating, adding water and ammonia water, reacting, filtering, washing and drying to obtain hydrophobic paraffin-silica microcapsules;
[0044] S3, adding bacterial cellulose into water to obtain a bacterial cellulose dispersion;
[0045] S4, after mixing methyltrimethoxysilane, water, tert-butyl alcohol and citric acid, adding the bacterial cellulose dispersion, and continuing to stir to obtain a bacterial cellulose-methyltrimethoxysilane dispersion;
[0046] S5, adding hydrophobic paraffin-silica microcapsules to a mixed solution of tert-butyl alcohol and water, dispersing by ultrasonication, and then adding bacterial cellulose-methyltrimethoxysilane dispersion to obtain a mixed solution;
[0047] S6. Directional freezing and freeze-drying the mixed solution in sequence to obtain a nanofiber composite aerogel.
[0048] The present invention prepares a nanofiber composite aerogel with certain mechanical properties, recycling performance, high adsorption capacity and high filtration efficiency through simple process design. Its innovation lies in: first, bacterial cellulose, microcapsules and methyltrimethoxysilane are compounded together for the first time to make aerogel; second, the compound of the three solves the problem of poor mechanical properties and recyclability of bacterial cellulose-based aerogels, and the three can be connected by physical or chemical bonds to form a porous cross-linked network, which provides a separation channel for separating liquids, wherein methyltrimethoxysilane acts as an adhesive, increases the cross-linking sites of bacterial cellulose to enhance the skeleton strength while improving its hydrophobic properties, and microcapsule nanoparticles increase its mechanical properties and adhere to bacterial cellulose fibers, which is expected to form a cavity structure by using it, and realize underwater double super-repellent through capillary effect combined with pre-wetting; third, a composite aerogel with macroporous orientation and multi-level pore structure can be obtained by directional freezing combined with freeze-drying technology, which provides a fast channel for separating liquids and improves flux. By adopting the in-situ method, microcapsule nanoparticles and methyltrimethoxysilane are added in situ, providing an integrated preparation scheme for synthesizing aerogels for oil-water separation.
[0049] In some embodiments, paraffin-silica microcapsules are prepared by emulsion polymerization, commonly known as the one-pot method. First, paraffin, deionized water and anhydrous ethanol are put into a three-necked flask, heated in an oil bath to melt, and tetraethyl orthosilicate and hexadecyltrimethylammonium bromide are added for emulsification for a certain period of time, and ammonia water is added to start the polymerization. Finally, the obtained reaction solution is centrifuged and filtered for washing, and the solid substance is placed in a constant temperature forced air drying oven to dry to obtain paraffin-silica microcapsules.
[0050] Specifically, paraffin, water and ethanol are mixed and heated to 50-90°C, preferably 75-80°C, to melt the paraffin, and then tetraethyl orthosilicate and hexadecyltrimethylammonium bromide are added and emulsified at 400-1000 r / min for 30-60 min, preferably, the emulsification speed is 700-800 r / min, and the emulsification time is 30-40 min; then ammonia water is added and reacted at 300-500 r / min for 1-2 h, preferably, the reaction speed is 40 0-450r / min, reaction time is 1.8-2h, filtering, washing, and drying to obtain paraffin-silica microcapsules; wherein the mass volume ratio of paraffin, tetraethyl orthosilicate, hexadecyltrimethylammonium bromide, water, ethanol, and ammonia water is (1-3)g:(1-3)g:(0.5-2)g:(55-60)mL:(25-30)mL:(0.5-2)mL, the mass concentration of ammonia water is 20-30%, and preferably, the mass concentration of ammonia water is 25%.
[0051] In some embodiments, hydrophobic paraffin-silica microcapsules can be prepared by the following steps: adding paraffin-silica microcapsules and methyltrimethoxysilane to anhydrous ethanol and stirring to disperse them evenly, then adding a certain amount of water and ammonia water in sequence to start the reaction, and similarly washing them three times by centrifugation with anhydrous ethanol to remove residual modifiers and other impurities such as ammonia water, and finally drying the product in a vacuum oven to obtain hydrophobically modified paraffin-silica-methyltrimethoxysilane microcapsules, that is, hydrophobic paraffin-silica microcapsules.
[0052] Specifically, paraffin-silica microcapsules, methyltrimethoxysilane and ethanol are mixed, heated to 40-60° C., water and ammonia water are added, reacted at 300-500 r / min for 10-15 hours, filtered, washed and dried to obtain hydrophobic paraffin-silica microcapsules; wherein the mass volume ratio of paraffin-silica microcapsules, methyltrimethoxysilane, ethanol, water and ammonia water is (1-4) g: (1-4) g: (55-65) g: (1-8) g: (0.5-2) mL, and the mass concentration of ammonia water is 20-30%.
[0053] Preferably, in the preparation process of hydrophobic paraffin-silica microcapsules, the mass ratio of methyltrimethoxysilane to paraffin-silica microcapsules is (1-2):(1-2), more preferably (1-1.2):1; the mass ratio of water to methyltrimethoxysilane is preferably 1:(1-2), more preferably (0.8-1):1; the reaction temperature is preferably 40-60°C, more preferably 40-45°C; the stirring speed is preferably 300-500r / min, more preferably 400-450r / min; the concentration of ammonia water for initiating polymerization is 25%wt, and the amount is preferably 0.5-1.2mL, more preferably 1.0-1.1mL.
[0054] In some embodiments, the mass concentration of the bacterial cellulose dispersion is 0.35-0.7%.
[0055] Specifically, the bacterial cellulose is dispersed in deionized water and mechanically stirred and crushed to obtain a bacterial cellulose dispersion; preferably, the mass concentration of the bacterial cellulose dispersion is 0.35-0.7%, more preferably 0.65%; preferably, the mechanical stirring speed is 10000-15000 r / min, more preferably 12000-14000 r / min, preferably, the stirring time is 50-80 min, more preferably 65-75 min.
[0056] In some embodiments, methyltrimethoxysilane, water, tert-butyl alcohol, and citric acid are stirred at 350-400 r / min for 40-50 min to obtain a methyltrimethoxysilane dispersion;
[0057] The methyltrimethoxysilane dispersion liquid is mixed with the bacterial cellulose dispersion liquid, and ultrasonically dispersed for 40 to 70 minutes to obtain a bacterial cellulose-methyltrimethoxysilane dispersion liquid;
[0058] Wherein, the mass ratio of methyltrimethoxysilane, water, tert-butyl alcohol and citric acid is (0.1-0.2):(5-6):(5-6):(0.04-0.05);
[0059] The mass ratio of methyltrimethoxysilane in the methyltrimethoxysilane dispersion to bacterial cellulose in the bacterial cellulose dispersion is (3-4):5.
[0060] Specifically, methyltrimethoxysilane and citric acid are dispersed in deionized water and tert-butanol, and a methyltrimethoxysilane dispersion is obtained by magnetic stirring; preferably, the stirring speed is 350-400 r / min, and the stirring time is 40-50 min; preferably, the mass ratio of deionized water to tert-butanol is (0.6-1):(0.6-1), and more preferably (0.9-1):1; the methyltrimethoxysilane dispersion is mixed with the bacterial cellulose dispersion, and ultrasonically dispersed to obtain a bacterial cellulose-methyltrimethoxysilane dispersion; preferably, the ultrasonic dispersion time is 40-70 min, and more preferably 50-60 min; the mass ratio of methyltrimethoxysilane to bacterial cellulose is (3-4):5, and preferably 4:5.
[0061] In some embodiments, hydrophobic paraffin-silica microcapsules are added to a mixed solution of tert-butyl alcohol and water, ultrasonically dispersed for 20 to 30 minutes, and then bacterial cellulose-methyltrimethoxysilane dispersion is added, and stirred at 350 to 400 r / min for 50 to 70 minutes to obtain a mixed solution;
[0062] Wherein, the mass ratio of hydrophobic paraffin-silica microcapsules, tert-butyl alcohol, and water is (0.1-0.135):(4-5):(4-5); preferably, the mass ratio is (0.1-0.135):4.71:4.71;
[0063] The mass ratio of hydrophobic paraffin-silica microcapsules to bacterial cellulose is (0.1-3):5.
[0064] Specifically, the hydrophobic paraffin-silicon dioxide microcapsules are uniformly dispersed with deionized water and tert-butanol by ultrasonic dispersion, and then bacterial cellulose-methyltrimethoxysilane dispersion is added, and mechanical stirring is performed to obtain a uniformly dispersed bacterial cellulose / microcapsule / methyltrimethoxysilane dispersion, i.e., a mixed solution; preferably, the mass ratio of hydrophobic paraffin-silicon dioxide microcapsules to bacterial cellulose is (0.1-3):5; preferably, the mass ratio of deionized water to tert-butanol is (0.6-1):(0.6-1), more preferably (0.9-1):1; preferably, the stirring speed is 350-400 r / min, and the stirring time is 50-70 min, more preferably 60-65 min.
[0065] In some embodiments, directional freezing specifically comprises:
[0066] The mixed liquid is placed in a mold, and the bottom of the mold is placed in a cold source for directional freezing;
[0067] Wherein, the material of the mold is a heat-conducting metal, preferably, the heat-conducting metal is copper or iron;
[0068] The cold source is liquid nitrogen, and the directional freezing time is 5 to 15 minutes, more preferably 7 to 12 minutes;
[0069] In some embodiments, the freeze-drying temperature is -20 to -60°C, and the freeze-drying time is 24 to 72 hours. Preferably, the freeze-drying temperature is -55 to -60°C, and the freeze-drying time is 48 to 72 hours.
[0070] Specifically, the above-mentioned directional freezing is a conventional technical means well known to those skilled in the art, which specifically involves immersing the mold in a liquid nitrogen environment, placing the mixed liquid in the mold, and performing unidirectional heat transfer at the bottom of the mold to freeze the water to form a directional distribution structure, and then agglomerating the mixed solution to obtain a frozen block.
[0071] In some embodiments, bacterial cellulose is obtained by the following processing steps: a certain mass of bacterial cellulose flakes are soaked in NaOH solution and then washed with deionized water to neutrality, and then pre-freeze-dried in a refrigerator, and then freeze-dried in a freeze dryer to obtain pure bacterial cellulose; preferably, the concentration of the NaOH solution used for soaking is 0.5-1.2 mol / L, more preferably 0.9-1.0 mol / L; preferably, the soaking time is 12-36 h, more preferably 24-30 h; the freeze-drying temperature is preferably -20--60 ° C, more preferably -45--60 ° C; the freeze-drying time is preferably 48-96 h, more preferably 72-96 h.
[0072] Based on the same inventive concept, the present invention also provides a method for preparing a nanofiber composite aerogel, which is prepared by the above-mentioned preparation method.
[0073] Based on the same inventive concept, the present invention also provides a nanofiber composite aerogel prepared by the above preparation method or the use of the above nanofiber composite aerogel as an adsorption material or an oil-water separation material.
[0074] The nanofiber composite aerogel prepared by the present invention is a microcapsule / bacterial cellulose-methyltrimethoxysilane composite aerogel (denoted as PCM / BC-MTMS), which has the following beneficial effects compared with the prior art:
[0075] First, the bacterial cellulose selected in the present invention is a kind of nanocellulose, which comes from microorganisms and has the advantages of wide sources, biodegradability, high purity, and good mechanical properties. And its surface has abundant hydroxyl groups, which makes it amphiphilic, and it is easy to undergo acid hydrolysis, cross-linking, esterification, silanization and other reactions to modify and improve practical performance. Bacterial cellulose aerogel combines the advantages of aerogel and bacterial cellulose, and has the advantages of low density, high porosity, and high specific surface area. There are many "pores" inside it. This structure provides a separation channel for separating liquids and provides abundant adsorption sites for adsorbing liquids.
[0076] Second, the present invention uses directional freezing to obtain a macroporous oriented structure, so that the microcapsule / bacterial cellulose-methyltrimethoxysilane macroporous oriented nanofiber composite aerogel has a higher specific surface area, significantly reduces the liquid passage path, thereby improving the flux of the composite aerogel, and compared with the non-macroporous oriented microcapsule / bacterial cellulose-methyltrimethoxysilane composite aerogel, the adsorption performance and oil-water separation performance of the oriented nanofiber composite aerogel are significantly improved. Moreover, the microcapsule / bacterial cellulose-methyltrimethoxysilane macroporous oriented nanofiber composite aerogel provided by the present invention also has a multi-level pore structure and fine nanofibers, which can provide more adsorption sites, can effectively adsorb organic matter in oily wastewater, and improve the oil-water separation performance and adsorption performance of the composite aerogel; in the process of obtaining a macroporous oriented structure by directional freezing, methyltrimethoxysilane tends to be concentrated at the nodes of the bacterial cellulose nanofibers. When the composite aerogel is subjected to external pressure, the stress is first concentrated at the nodes, effectively alleviating the stress breakage of the bacterial cellulose nanofibers, so that the composite aerogel has excellent resilience, and at the same time gives the composite aerogel excellent hydrophobicity and recyclability.
[0077] Third, the microcapsules are coated on the nanofibers to form a reentrant cavity structure, which is more conducive to the formation of a stable liquid film after the aerogel is pre-wetted by the liquid and reaches a metastable state, thus hopefully realizing underwater dual superphobicity.
[0078] Fourth, the preparation process is simple and easy to operate, the raw materials used are low in toxicity, green and environmentally friendly, the production cost is low, and it is suitable for industrial production.
[0079] The following further describes the nanofiber composite aerogel of the present application and its preparation method and application with specific examples. This section further describes the content of the present invention in conjunction with specific examples, but should not be construed as limiting the present invention. Unless otherwise specified, the technical means used in the examples are conventional means known to those skilled in the art. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0080] Example 1
[0081] This embodiment provides a method for preparing a nanofiber composite aerogel, comprising the following steps:
[0082] S1, paraffin-silica microcapsules (PW@SiO 2 ), comprising the following steps: 2 g of paraffin wax, 57 mL of water and 28.5 mL of ethanol are placed in a 500 mL three-necked flask and mixed, and then heated in an oil bath at 80°C to melt the paraffin wax, and then 2 g of tetraethyl orthosilicate (TEOS) and 1 g of hexadecyltrimethylammonium bromide (CTAB) are added and emulsified at 800 r / min for 30 min, and then 1 mL of ammonia water with a mass concentration of 25% is added to start polymerization, and the reaction is carried out at 400 r / min for 2 h, the solution after the reaction is centrifuged and filtered, and after washing, the solid product is placed in a constant temperature blast drying oven and dried at 35°C for 12 h to obtain a white powder (2.4 g), which is the paraffin-silica microcapsule;
[0083] S2、PW@SiO 2 The hydrophobic modification comprises the following steps: adding 2.4 g of paraffin-silica microcapsules and 2.4 g of methyltrimethoxysilane (MTMS) to 60 g of ethanol, heating to 40° C. and stirring at 400 r / min, then sequentially adding 4.8 g of water and 1 mL of 25% ammonia water, and reacting for 12 h; washing the reaction product, and drying it in a vacuum oven for 12 h to obtain a white powder as the target product PW@SiO 2 -MTMS, i.e. hydrophobic paraffin-silica microcapsules;
[0084] S3, place bacterial cellulose sheets (purchased from Hainan Yide Food Co., Ltd.) in 1 mol L -1 Soak in a NaOH solution for 24 hours, then wash with deionized water until neutral; then place the soaked bacterial cellulose flakes in a -2°C refrigerator for pre-freeze drying for 24 hours, then place in a freeze dryer and freeze at -45°C for 72 hours to obtain pure bacterial cellulose;
[0085] 0.225 g of pure bacterial cellulose was dispersed in deionized water, and mechanically stirred at 13000 r / min for 70 min to obtain a bacterial cellulose dispersion liquid; the mass concentration of the bacterial cellulose dispersion liquid was 0.65%;
[0086] S4, 0.18 g of methyltrimethoxysilane, 0.045 g of citric acid, 5.2 g of water, and 5.2 g of tert-butyl alcohol were stirred at 380 r / min for 45 min to obtain a methyltrimethoxysilane dispersion;
[0087] The methyltrimethoxysilane dispersion and the bacterial cellulose dispersion in S3 were stirred at 1500 r / min for 20 min, and then ultrasonically dispersed for 50 min to obtain a bacterial cellulose-methyltrimethoxysilane dispersion;
[0088] S5, adding 0.0675g of hydrophobic paraffin-silica microcapsules to a mixed solution of 4.71g of tert-butyl alcohol and 4.71g of water, ultrasonically dispersing for 30min, then adding the bacterial cellulose-methyltrimethoxysilane dispersion in S4, stirring at 380r / min for 60min to obtain a mixed solution; wherein the mass of the hydrophobic paraffin-silica microcapsules is 30% of the mass of the bacterial cellulose (0.0675 / 0.225=30%);
[0089] S6, the mixed solution is sequentially subjected to directional freezing and freeze drying to obtain PW@SiO 2 -MTMS / BC-MTMS nanofiber composite aerogel (denoted as PCM / BC-MTMS-30);
[0090] Among them, directional freezing specifically includes:
[0091] The mixed liquid is placed in a mold, and the bottom of the mold is placed in a cold source for directional freezing;
[0092] The mold material is copper; the cold source is liquid nitrogen, and the directional freezing time is 10 minutes;
[0093] The freeze-drying temperature was -60°C and the freeze-drying time was 60 h.
[0094] Example 2
[0095] The preparation method of the nanofiber composite aerogel provided in this embodiment is the same as that in Embodiment 1, except that in step S5, the mass of the hydrophobic paraffin-silicon dioxide microcapsule is 0.09 g, the mass of the hydrophobic paraffin-silicon dioxide microcapsule is 40% (0.09 / 0.225=40%) of the mass of the bacterial cellulose, and the other process parameters are the same as those in Embodiment 1; PW@SiO 2 -MTMS / BC-MTMS nanofiber composite aerogel is recorded as PCM / BC-MTMS-40.
[0096] Example 3
[0097] The preparation method of the nanofiber composite aerogel provided in this embodiment is the same as that in Embodiment 1, except that in step S5, the mass of the hydrophobic paraffin-silicon dioxide microcapsule is 0.1125 g, the mass of the hydrophobic paraffin-silicon dioxide microcapsule is 50% of the mass of the bacterial cellulose (0.1125 / 0.225=50%), and the other process parameters are the same as those in Embodiment 1; PW@SiO2 -MTMS / BC-MTMS nanofiber composite aerogel is recorded as PCM / BC-MTMS-50.
[0098] Example 4
[0099] The preparation method of the nanofiber composite aerogel provided in this embodiment is the same as that in Embodiment 1, except that in step S5, the mass of the hydrophobic paraffin-silicon dioxide microcapsule is 0.135 g, the mass of the hydrophobic paraffin-silicon dioxide microcapsule is 60% (0.135 / 0.225=60%) of the mass of the bacterial cellulose, and the other process parameters are the same as those in Embodiment 1; PW@SiO 2 -MTMS / BC-MTMS nanofiber composite aerogel is recorded as PCM / BC-MTMS-60.
[0100] Comparative Example 1
[0101] The preparation method of the nanofiber composite aerogel provided in this comparative example 1 is the same as that in Example 1, except that in step S5, no hydrophobic paraffin-silicon dioxide microcapsules are added. The specific preparation method comprises the following steps:
[0102] S1. Place the bacterial cellulose sheet in 1 mol L -1 Soak in a NaOH solution for 24 hours, then wash with deionized water until neutral; then place the soaked bacterial cellulose flakes in a -2°C refrigerator for pre-freeze drying for 24 hours, then place in a freeze dryer and freeze at -45°C for 72 hours to obtain pure bacterial cellulose;
[0103] The pure bacterial cellulose was dispersed in deionized water and mechanically stirred at 13000 r / min for 70 min to obtain a bacterial cellulose dispersion liquid; the mass concentration of the bacterial cellulose dispersion liquid was 0.65%;
[0104] S2, stirring methyltrimethoxysilane, citric acid, water, and tert-butyl alcohol at 380 r / min for 45 min to obtain a methyltrimethoxysilane dispersion;
[0105] The methyltrimethoxysilane dispersion and the bacterial cellulose dispersion in S3 were stirred at 1500 r / min for 20 min, and then ultrasonically dispersed for 50 min to obtain a bacterial cellulose-methyltrimethoxysilane dispersion;
[0106] S3, after mixing tert-butyl alcohol and water, ultrasonically disperse them for 30 minutes, then add the bacterial cellulose-methyltrimethoxysilane dispersion in S2, and stir at 380r / min for 60 minutes to obtain a mixed solution; S6, sequentially perform directional freezing and freeze-drying on the mixed solution to obtain BC-MTMS nanofiber composite aerogel (referred to as BC-MTMS);
[0107] Among them, directional freezing specifically includes:
[0108] The mixed liquid is placed in a mold, and the bottom of the mold is placed in a cold source for directional freezing;
[0109] The mold material is copper; the cold source is liquid nitrogen, and the directional freezing time is 10 minutes;
[0110] The freeze-drying temperature was -60°C and the freeze-drying time was 60 h.
[0111] Performance Testing
[0112] Scanning electron microscope test
[0113] Figure 1 PW@SiO prepared in Example 1 2 -Scanning electron microscopy image of MTMS.
[0114] from Figure 1 It can be seen that the size of the hydrophobically modified paraffin-silica microcapsules is about 400-450 nm and is a regular spherical shape.
[0115] Figure 2 The scanning electron microscope images of the nanofiber composite aerogels prepared in Examples 1 to 4 and Comparative Example 1 at different magnifications are shown in FIG. 1 -a 3 ) is BC-MTMS, (b 1 -b 3 ) is PCM / BC-MTMS-30, (c 1 -c 3 ) is PCM / BC-MTMS-40, (d 1 -d 3 ) is PCM / BC-MTMS-50, (e 1 -e 3 ) is PCM / BC-MTMS-60.
[0116] Depend on Figure 2 It can be seen that the nanofiber composite aerogels prepared by the present invention all have a skeleton macroporous orientation in one direction, and many fine long filaments are intertwined and interspersed in the composite aerogel to form a loose and porous structure. The average diameter of the aerogel filaments prepared in Comparative Example 1 is basically at the nanometer level, lacking micrometer-level fiber bundles and pore structures. After the introduction of hydrophobically modified paraffin-silicon dioxide microcapsule particles, the bacterial cellulose composite aerogel not only has nanometer-level filaments, but also micrometer-level fiber bundles. Figure 2It also shows that nano-scale cellulose fibrils and micron-scale fiber bundles are entangled with each other to form a porous rough structure. Due to hydrogen bonding and chemical interactions, MTMS can cross-link bacterial cellulose nanofibers and microcapsule nanoparticles, and make some nanoparticles adhere to the fiber surface, constructing a multi-level porous structure aerogel with skeleton-oriented macropores.
[0117] Contact angle test
[0118] Test method: Wetting related tests were performed using an OCA25 optical contact angle meter. When testing the contact angle in the air, drop 3 μL of water on the aerogel surface, and record the contact angle after the water drop is stationary on the aerogel surface for 3 seconds. When testing the contact angle of water under oil, the aerogel needs to be pretreated, as follows: Soak the dry aerogel in 30 mL of n-hexane for 1 hour. At this time, the aerogel completely sinks to the bottom of the solvent and no bubbles emerge, and the oil-water test sample is obtained. Then place it in a glass box filled with n-hexane, drop 3 μL of water on the aerogel surface, and record the oil-water contact angle. Figure 3 The contact angle test results of the nanocomposite aerogels prepared in Examples 1 to 4 and Comparative Example 1 are shown; Figure 3 Medium CA W Represents the contact angle of different nanocomposite aerogels in air after water is dropped on the surface; CA W / O represents the water contact angle of different nanocomposite aerogels under oil.
[0119] Depend on Figure 3 It can be seen that the nanocomposite aerogels prepared in the examples of the present invention and the comparative examples have obvious hydrophobicity and hydrophobicity under oil. The nanocomposite aerogels obtained in Examples 2 and 3 have super hydrophobicity under oil.
[0120] Oil-water separation performance test
[0121] Test method: Prepare a mixed solution of heavy oil and water, and use Sudan III to dye; the mass ratio of heavy oil to water is 4:1, and the heavy oil is dichloromethane; use a syringe to perform an oil-water separation experiment, pour the mixed solution onto the nanocomposite aerogel prepared in Examples 1 to 4 and Comparative Example 1, and separate the oil and water by the liquid's own gravity. The aerogel needs to be pretreated before separation, and the dried aerogel is soaked in 30mL of dichloromethane for 1h. The aerogel filtration efficiency η can be calculated by the following formula:
[0122]
[0123] In the formula, η represents the filtration efficiency, m 0 and m 1 are the mass of oil before and after separation, respectively.
[0124] The oil flux of aerogel can be calculated by the following formula:
[0125]
[0126] Where Flux represents the oil flux of aerogel, Δv is the volume of oil passing through, Δt represents the time taken for oil with a volume of Δv to pass through, and s represents the effective filtration area.
[0127] In order to study the reusability of aerogels, 10 separation-recovery cycle tests were carried out. After each test, the sample was washed with ethanol before the next test.
[0128] Figure 4 The oil-water separation test results of the composite aerogels prepared in Examples 1 to 3 and Comparative Example 1 are shown in FIG. Figure 4 (a) It can be seen that the separation efficiency (i.e., filtration efficiency) of the composite aerogels prepared in Examples 1 to 3 and Comparative Example 1 is greater than 99%, and the separation efficiency only slightly decreases after ten cycles. Figure 4 (b) It can be seen that the oil fluxes prepared in Examples 1 to 3 and Comparative Example 1 are 1.08×10 3 , 2.51×10 3 , 2.79×10 3 , 0.53×10 3 (L m -2 h -1 ), the oil flux of the capsule / bacterial cellulose-methyltrimethoxysilane macroporous oriented nanofiber composite aerogel prepared in the embodiment of the present invention is higher than that of the nanofiber composite aerogel prepared in comparative example 1.
[0129] Adsorption performance test
[0130] Test method: Using a variety of oily organic solvents (including n-hexane, xylene, petroleum ether, ethanol, and dichloromethane (DCM)), the aerogel sample PCM / BC-MTMS-50 prepared in Example 3 was first immersed in 30 mL of different oily organic solvents and allowed to stand for 1 hour so that the sample was completely soaked in the oily organic solvent. Then the aerogel sample was taken out and weighed. The ability of the aerogel sample to adsorb oil can be calculated by the following formula:
[0131]
[0132] Where c represents the oil absorption capacity of the aerogel sample, m a and m b are the masses of the aerogel sample before and after absorbing the oily organic solvent, respectively.
[0133] Figure 5The adsorption performance test results of PCM / BC-MTMS-50 are shown in Figure 2. Figure 5 It can be seen that the PCM / BC-MTMS-50 prepared in the present invention has a high oil absorption capacity, which can reach 57-114 times of its own weight, and has particularly excellent adsorption performance for dichloromethane.
[0134] Mechanical properties test
[0135] Test method: Use 68TM-10 universal material testing machine, equipped with 50N sensor, at a rate of 1mm min -1 Loading and unloading to test the compression resilience of the aerogel. The composite aerogels prepared according to the methods of Examples 1 to 4 and Comparative Example 1 were processed into cylindrical aerogel samples (about 18.5 mm in diameter and 6 mm in height), and the compression resilience of the aerogel samples was tested at strains of 40%, 60%, and 80%, respectively.
[0136] Figure 6 The results of the resilience test of the composite aerogels prepared in Examples 1 to 4 and Comparative Example 1 are shown in FIG. Figure 6 It can be seen that the composite aerogel prepared in the present invention has excellent resilience before the strain reaches 40%.
[0137] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a nanofiber composite aerogel, characterized in that: The following steps are involved: After paraffin, water and ethanol are mixed, the paraffin is heated to melt, tetraethyl orthosilicate and hexadecyltrimethylammonium bromide are added for emulsification, and then ammonia water is added for reaction, filtered, washed and dried to obtain paraffin-silicon dioxide microcapsules; paraffin-silica microcapsules, methyltrimethoxysilane and ethanol are mixed, heated, and then water and ammonia water are added to react, filtered, washed and dried to obtain hydrophobic paraffin-silica microcapsules; adding bacterial cellulose into water to obtain a bacterial cellulose dispersion; After mixing methyltrimethoxysilane, water, tert-butyl alcohol and citric acid, the bacterial cellulose dispersion is added and the stirring is continued to obtain a bacterial cellulose-methyltrimethoxysilane dispersion; Adding hydrophobic paraffin-silica microcapsules to a mixed solution of tert-butyl alcohol and water, dispersing by ultrasonication, and then adding bacterial cellulose-methyltrimethoxysilane dispersion to obtain a mixed solution; The mixed solution is sequentially subjected to directionally freezing and freeze-drying to obtain a nanofiber composite aerogel.
2. The method for preparing the nanofiber composite aerogel according to claim 1, characterized in that: Paraffin, water and ethanol are mixed and heated to 50-90°C to melt the paraffin, and then tetraethyl orthosilicate and hexadecyltrimethylammonium bromide are added and emulsified at 400-1000 r / min for 30-60 min, and then ammonia water is added and reacted at 300-500 r / min for 1-2 h, filtered, washed and dried to obtain paraffin-silicon dioxide microcapsules; wherein the mass volume ratio of paraffin, tetraethyl orthosilicate, hexadecyltrimethylammonium bromide, water, ethanol and ammonia water is (1-3) g: (1-3) g: (0.5-2) g: (55-60) mL: (25-30) mL: (0.5-2) mL, and the mass concentration of ammonia water is 20-30%.
3. The method for preparing the nanofiber composite aerogel according to claim 1, characterized in that: Paraffin-silica microcapsules, methyltrimethoxysilane and ethanol are mixed, heated to 40-60° C., water and aqueous ammonia are added, reacted at 300-500 r / min for 10-15 hours, filtered, washed and dried to obtain hydrophobic paraffin-silica microcapsules; wherein the mass volume ratio of paraffin-silica microcapsules, methyltrimethoxysilane, ethanol, water and aqueous ammonia is (1-4) g: (1-4) g: (55-65) g: (1-8) g: (0.5-2) mL, and the mass concentration of aqueous ammonia is 20-30%.
4. The method for preparing the nanofiber composite aerogel according to claim 1, characterized in that: The mass concentration of the bacterial cellulose dispersion is 0.35-0.7%.
5. The method for preparing the nanofiber composite aerogel according to claim 1, characterized in that: Stir methyltrimethoxysilane, water, tert-butyl alcohol and citric acid at 350-400 r / min for 40-50 min to obtain a methyltrimethoxysilane dispersion; The methyltrimethoxysilane dispersion liquid is mixed with the bacterial cellulose dispersion liquid, and ultrasonically dispersed for 40 to 70 minutes to obtain a bacterial cellulose-methyltrimethoxysilane dispersion liquid; Wherein, the mass ratio of methyltrimethoxysilane, water, tert-butyl alcohol and citric acid is (0.1-0.2):(5-6):(5-6):(0.04-0.05); The mass ratio of methyltrimethoxysilane in the methyltrimethoxysilane dispersion to bacterial cellulose in the bacterial cellulose dispersion is (3-4):
5.
6. The method for preparing the nanofiber composite aerogel according to claim 1, characterized in that: Adding hydrophobic paraffin-silica microcapsules to a mixed solution of tert-butyl alcohol and water, ultrasonically dispersing for 20 to 30 minutes, then adding bacterial cellulose-methyltrimethoxysilane dispersion, stirring at 350 to 400 r / min for 50 to 70 minutes to obtain a mixed solution; Wherein, the mass ratio of hydrophobic paraffin-silica microcapsules, tert-butyl alcohol, and water is (0.01-0.135):(4-5):(4-5); The mass ratio of hydrophobic paraffin-silica microcapsules to bacterial cellulose is (0.1-3):
5.
7. The method for preparing the nanofiber composite aerogel according to claim 1, characterized in that: The directional freezing specifically includes: The mixed liquid is placed in a mold, and the bottom of the mold is placed in a cold source for directional freezing; The mold is made of heat-conducting metal, the cold source is liquid nitrogen, and the directional freezing time is 5 to 15 minutes.
8. The method for preparing the nanofiber composite aerogel according to claim 1, characterized in that: The freeze drying temperature is -20 to -60°C, and the freeze drying time is 24 to 72 hours.
9. A nanofiber composite aerogel, characterized in that: The preparation method is as described in any one of claims 1 to 8.
10. Use of the nanofiber composite aerogel prepared by the method according to any one of claims 1 to 8 or the nanofiber composite aerogel according to claim 9 as an adsorption material or an oil-water separation material.
Citation Information
Patent Citations
Hierarchical pore silicon dioxide aerogel material and preparation method thereof
CN114180582A
Elastic bacterial cellulose composite aerogel capable of adjusting structure by using absolute ethyl alcohol as well as preparation method and application of elastic bacterial cellulose composite aerogel
CN115960384A